Danggui-Shaoyao-San Can Ameliorate Alzheimer’s Disease by Inhibiting Hippocampal Neuron Apoptosis: Findings from Serum Pharmacology - Zhang KX; Zhang JW; Jiang YH; Wang YR; Liu ZL; Ding PL; Wang XY; Cui WQ; Xu XQ; Wang YH (Drug Design, Development and Therapy)
Kai-Xin Zhang,1 Ji-Wei Zhang,2 Yan-Hong Jiang,1 Yi-Ran Wang,1 Zhen-Ling Liu,1 Peng-Li Ding,1 Xiang-Ying Wang,1 Wen-Qiang Cui,3 Xiang-Qing Xu,3,* Ya-Han Wang3,* 1First College of Clinical Medicine, Shandong University of Traditional Chinese Medicine, Jinan, 250000, People’s Republic of China; 2College of Acupuncture and Massage, Shandong University of Traditional Chinese Medicine, Jinan, 250000, People’s Republic of China; 3Department of Neurology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, 250000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiang-Qing Xu, Ya-Han Wang; Department of Neurology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, 250000, People’s Republic of China, Email happyxiangqing@163.com; sdwangyahan@sina.comBackground: Danggui-Shaoyao-San (DSS) is a traditional Chinese medicine prescription with a history of nearly 2000 years, originally widely used for gynecological diseases, and in recent years research has found that DSS also has a good therapeutic effect on Alzheimer’s disease (AD).Purpose: The objective is to investigate the metabolic components of the DSS in the blood and the potential mechanisms for AD.Materials and Methods: Liquid chromatography‒mass spectrometry (LC-MS) combined with gas chromatography‒mass spectrometry (GC-MS) based non-targeted metabolomics were used to conduct in-depth research. Serum Pharmacology was used to analyze potential mechanisms of DSS for AD. C57BL/6J mice and Hippocampal neuronal cell line (HT-22) were used to prepare the AD model. Enzyme linked immunosorbent assay (Elisa), quantitative polymerase chain reaction (q-PCR), Morris water maze,Western blot (WB), Immunohistochemical and Immunofluorescence were used to study the effect of DSS on AD. Flow cytometry and Cell Counting Kit-8 (CCK-8) reveal the effect of DSS serum on HT-22 proliferation and apoptosis.Results: A total of 57 metabolic components were screened in DSS serum. Serum Pharmacology revealed that the calcium signaling pathway and cAMP/PKA/CREB pathway may be a potential mechanism through which DSS treated AD. DSS can reduce aberrant phosphorylation of Tau and modulates cAMP/PKA/CREB pathway to improve cognition and apoptosis in AD mice. DSS serum can increase the cell viability of HT-22 and reduce apoptosis mainly by alleviating mitochondrial calcium overloading.Conclusion: DSS can modulate the calcium signaling pathway and enhance the cAMP/PKA/CREB signaling pathway to ameliorate Tau aberrant phosphorylation, cognitive deficits and neuronal apoptosis after AD. Keywords: Alzheimer’s disease, calcium signaling pathway, cAMP/PKA/CREB signaling pathway, Danggui-Shaoyao-San, apoptosis, serum pharmacology